Voos ficcionais: imagens de ficção e de escritor em "O vôo da madrugada" de Sérgio Sant'Anna - Aquino, Fernanda Nali de (2017)
This work investigates the relations between six narratives of Sérgio Sant'Anna included in "O voo da madrugada", penultimate book of short stories published by the writer in 2003. The objective was to verify a panel of that moment of the work of Sant'Anna through a reading of literature approach with limit experiences of death, sexuality and artistic expression to think of them as transgression, contributing to broaden the reflections on the fictional texts of this writer who has become Indispensable for thinking about literature in Brazil. We will see how these themes are approached in these narratives trying to point out images that are drawn in them and how they dialogue with a certain literary tradition, leading to an image of literature and contemporary writer, which consolidates a process of hybrid composition that we can call Brief Forms. We used conceptions especially of Michel Foucault, Giorgio Agamben and Ricardo Piglia.